2008
DOI: 10.4238/vol7-3gmr376
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of DNA repair polymorphisms with histopathological characteristics and hormone receptors in a group of Brazilian women with breast cancer

Abstract: ABSTRACT. The association of tumor differentiation and estrogen receptor expression with the prognosis of breast cancer has been well established. Nevertheless, little is yet reported about the association of morphological characteristics of the tumor, estrogen receptor status and polymorphisms in low penetrance genes. The aim of the present study was to investigate a possible association between DNA repair gene polymorphisms (XRCC1, XPD, XRCC3, and RAD51) with histological type, grade and hormone receptor exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
4
13
1
1
Order By: Relevance
“…Out of the 100 abstracts retrieved through the search criteria, fifty-four were irrelevant, nine articles were excluded because they were conducted on other XRCC3 polymorphisms. Four studies (Bewick et al, 2006;Popanda et al, 2006;Dufloth et al, 2008;Falvo et al, 2011)was excluded given that it has not included controls , seven articles were reviews or meta-analyses. As a result, 26 case-control articles involving 36 studies were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 100 abstracts retrieved through the search criteria, fifty-four were irrelevant, nine articles were excluded because they were conducted on other XRCC3 polymorphisms. Four studies (Bewick et al, 2006;Popanda et al, 2006;Dufloth et al, 2008;Falvo et al, 2011)was excluded given that it has not included controls , seven articles were reviews or meta-analyses. As a result, 26 case-control articles involving 36 studies were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to this even European population didn't show any association with XRCC1 399 polymorphism in lung cancer patients (Lopez-Cima et al, 2007) and in bladder patients (Kelsey et al, 2004). Some studies have also demonstrated a strong association of the Arg399Gln XRCC1 polymorphism with an increased risk of breast cancer (Chacko, 2005;Dufloth et al, 2008;Sterpone et al, 2010). However in 2006, the Breast Cancer Association Consortium, as well as a large meta-analysis, reported no evidence of its association with breast cancer development (Breast Cancer Association Consortium, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies were manually searched in the reference list of all studies identified. Eligible studies had genotypic data with a casecontrol design and duplicates of previous studies were excluded [16]. As a result, we have identified a total of 33 eligible articles, which investigated the association of one or both polymorphisms, Asp312Asn and Lys751Gln, with breast cancer risk where 29 studied a single ethnic population.…”
Section: Selection Of Studiesmentioning
confidence: 99%